Tolerance as Cross-Cultural Communication among Religions in Indonesia - Yuliastuti, M. Hum., Dra Anicleta; Pujimahanani, S. S., M. Si., Cahyaningsih (Dinamika : Jurnal Sastra dan Budaya, 2020)
Abstract Indonesia, without question consists of various ethnicities, culture, and also religions. This country is so plural that identities may appreciate, correlate, and live together asa nation despite many differences within. They communicate as human beings with different understandings. Differences may be burdens to communicate, but these also indicate potential to shape dialogues between one and another. The dialogues then show tolerance among Indonesians. This paper would like to answer; how tolerance be reflected in cross-cultural communication among religions in Indonesia? By using qualitative descriptive method, this research asserts plural realities of Indonesia, cross-cultural communication, and tolerance among people. Tolerance itself is such an active mode of communication. People do not only talk in language but also speak through their identities towards other in everyday life. It is like constructivism which believes in own identities but also practice its thoughts to others. People are bound in their identities because those are what they believe. Meanwhile, people are related to others' identities because they live respectfully. It is true that tolerance is such an ethical deed of Indonesian people. Despite differences and many restrictions in religions, culture, or even politics, Indonesians respect each other in necessary ways. Even their own identities are used to practice goodness towards others too. In conclusion, tolerance is how to speak cross-cultural communication among Indonesian people. As a nation, people appreciate each other as everyone has the same right. As religious persons, their religions push Indonesians to do good deeds towards others too. Keywordscross-cultural communication, culture, religion, tolerance